Physicochemical property, bacterial diversity, and volatile profile during ripening of naturally fermented dry mutton sausage produced from Jianzhou big-eared goat - Chen, Juan; Niu, Ying; Wang, Jie; Yang, Ziyao; Cai, Zijian; Dao, Xiaofang; Wang, Chengen; Wang, Yong; Lin, Yaqiu (Frontiers in Microbiology, 2022)
Physicochemical properties, bacterial communities and volatile compounds of mutton sausage produced from Jianzhou Big-eared goat meat during natural ripening were investigated. Firmicutes and Bacteroidetes accounted for over 66% of all operational taxonomic units (OTUs) throughout the whole process, with Lachnospiraceae_NK4A136_group and Staphylococcus as the predominant genus during the early and later ripening period, respectively. The evolution of microbial composition became less rich and diverse. Uncultured bacterium, Lachnospiraceae_NK4A136_group and Staphylococcus were marker bacteria on day 0, 7 and 26, respectively, with none on day 6. The bacteria distribution seemed to influence the volatile profile of mutton sausage throughout processing, with the bacterial composition on day 0 and day 7 clustered separately from day 16 and day 26, and the same pattern for volatile profile. In the meanwhile, the concentration of total volatile fraction significantly increased and majorities of volatile compounds was generated during late ripening. Most aldehydes from lipid autooxidation, 3-methylbutanal, γ-dodecalactone, 2-pentylfuran and 1-octen-3-ol were key volatile compounds, contributing to the overall mutton sausage flavors. Based on Spearman’s correlation analysis, Staphylococcus as well as Psychrobacter were positively correlated with the production of the key volatile compounds, and other bacteria such as Lachnospiraceae_NK4A136_group, Bacteroides, Lactobacillus, Prevotella_1, Odoribacter and so on were associated with the production of most alcohols and esters.